2023
DOI: 10.1259/bjr.20220685
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deep learning on radiologists’ and radiology residents’ performance in identifying esophageal cancer on CT

Abstract: Objective: To investigate the effectiveness of a deep learning model in helping radiologists or radiology residents detect esophageal cancer on contrast-enhanced CT images. Methods: This retrospective study included 250 and 25 patients with and without esophageal cancer, respectively, who underwent contrast-enhanced CT between December 2014 and May 2021 (mean age, 67.9 ± 10.3 years; 233 men). A deep learning model was developed using data from 200 and 25 patients with esophageal cancer as training and validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…However, our experimental results suggested that the DL can also assist radiologists in improving the workups of esophageal cancers by reducing FPs and FNs in non-contrast chest CT scans. In particular, the DL model may improve the performance of junior radiologists to the senior level, which resonates with the conclusion of the studies ( 33 , 35 ). Accordingly, this may shed light on the early detection of esophageal cancers, especially in the context of health check-up examinations.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…However, our experimental results suggested that the DL can also assist radiologists in improving the workups of esophageal cancers by reducing FPs and FNs in non-contrast chest CT scans. In particular, the DL model may improve the performance of junior radiologists to the senior level, which resonates with the conclusion of the studies ( 33 , 35 ). Accordingly, this may shed light on the early detection of esophageal cancers, especially in the context of health check-up examinations.…”
Section: Discussionsupporting
confidence: 71%
“…The detection of early-stage esophageal cancer can be very challenging for both the radiologist and the DL model (such as Figure 6), but it is important for clinical practice. Referencing the other studies (33,36), the contrast-enhanced CT images may provide more information about esophageal cancer from early to late stage than the non-contrast images. Accordingly, we will consider incorporating contrast-enhanced CT to augment the capability of the DL model.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…9 Recently, deep-learning applications have gained wide attention in the field of radiology. [10][11][12] Recent studies have demonstrated that deep learning is applicable to both imaging diagnosis [13][14][15] and image processing. 16 Deep-learning reconstruction (DLR) is one such method, which employed deep convolutional neural network to improve image quality.…”
Section: Introductionmentioning
confidence: 99%